Pengembangan Media Pembelajaran Monopoli untuk Meningkatkan Kemampuan Menulis Teks Anekdot bagi Siswa Kelas X MAN Dairi - Kabeakan, Nuraini; Rambe, Riris Nurkholidah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
Writing ability is the pinnacle of productive language skills and is also a major challenge for students. The gap in the field shows a mismatch between curriculum demands and the reality at MAN Dairi, where the interest and ability of grade X students in writing anecdotal texts are still relatively low due to the use of conventional and monotonous learning media. This study aims to develop, validate, and test the practicality and effectiveness of modified monopoly learning media as an interactive solution in improving anecdotal text writing skills. The method applied in this study is Research and Development (R&D) with a development model following the 4D stages (Define, Design, Development, and Dissemination). The main findings show that the developed monopoly media meets the criteria for being very feasible based on expert validation with an average percentage of 88.3%. The results of the practicality test also showed a positive response with a percentage of 78.78% from students (practical category) and 90% from teachers (very practical category). Furthermore, the results of the effectiveness test through N-Gain score analysis obtained an average value of 0.8081 (80.80%) which is included in the high criteria. The conclusion of this study is that the modified monopoly learning media is proven to be valid, practical, and very effective in accelerating anecdotal text writing skills and fostering active student participation in a fun way.